Gender Aspects of Work and Management In Indian Companies - Katamreddy, Deepthi Reddy (2008)
This study aims to highlight some of the gender aspects of work and management in Indian companies. The primary motivation behind this study has been the tremendous progress made by companies in the UK in instituting Equal Opportunity policies and adopting appropriate steps to ensure that irrespective of the individual differences between the employees, they are not discriminated on the basis of their age, gender, ethnicity, physical disability etc. and are given equal opportunities in their work situation. While the issue of equal opportunity is vast, this study has been restricted to the study of women as one of the significant groups in the workforce. The study has been segregated into three parts. First, literature on equal opportunity and diversity management has been studied to understand the issues involved. The basic objective here is to understand the reason why women are discriminated against and the nature of discrimination that they face in their work situation and the lesson that organizations can learn from the experience of others in managing an increasingly diverse workforce comprising women and people from ethnic minority groups. Second, the status of women in Indian labour force has been studied based on the existing literature. Finally, a survey has been conducted to capture the perception of women employees in India about the various policies that their organizations have undertaken and how adequate these policies are for them to feel that they are not discriminated against.